THE EFFECT OF SERVICE QUALITY OF ELECTRONIC TAXING SYSTEM AND TAX EMPLOYEE COMPETENCE ON TAXPAYER SATISFACTION - Tri Wulanjayanti; Darman Usman (Jurnal Akuntansi, 2017)
This study aims to test the effect of service quality of electronic taxing system and tax employee competence on taxpayer satisfaction. The variables on this study was measured by using questionnaire. The sample of this study is personal Taxpayer who is running business activities and is registered at the Primary Tax Office of Bengkulu. The data used in this study is primary data. The hypothesis of the study is tested by using Multiple Linear Regression Analysis with the assistance of SPSS. The result of this study revealed that the service quality of electronic taxing system and tax employee competence had positive effect on the taxpayer satisfaction.Key Words: Service Quality of Electronic Taxing System, Tax Employee Competence, and Taxpayer Satisfaction.